Influence of thermal conductivity cf electrodes on EDM process parameters - Khan, Ahsan Ali; Mohammed , Baba Ndaliman; Md. Soot, Hamizah; Ishak, Norazah (INSI Publications, 2012)
Electrical Discharge machining (EDM) is a thermal process in which sparks discharging with high energy density at high temperatures are used to melt and evaporate a small amount of workpiece. Under this condition, both the cutting tool (electrode) and the workpiece are subjected to very intensive heat energy generated in the system, and thus implying that thermal conductivity might play a role in the process. This paper reports the results of an investigation on the influence of thermal conductivity of electrode material on EDM process parameters. The parameters investigated were material removal rate (MRR), electrode wear ratio (EWR) and surface roughness (Ra) of the machined surface. Three types Copper-tungsten (Cu-W) electrodes of different thermal conductivities were used in machining stainless steel workpiece. Their thermal conductivities are 2.40 Wcm¯¹ °C¯¹, 2.01 W cm¯¹ °C¯¹ and 1.82 W cm¯¹ °C¯¹. The three different levels of peak current applied were 1.5A, 3.5A and 6.5A. The results of the machining showed that the MRR was found to be highest at thermal conductivity of 1.82 W cm¯¹ °C¯¹ and discharge current of 6.5 A. Investigations also indicate that the influence of the electrodes’ thermal conductivity is more pronounced on the MRR, as it shows that there is interaction effect with the peak current on it. The maximum EWR of about 3.36 % was obtained with the current of 4.5 A, and subsequently reduces with further increase in the current. The surface finish of work material was found to be the best at the current of 1.5A and thermal conductivity of 1.82W cm¯¹ °C¯¹.